Intensitas Modal, Risiko Litigasi, Kepemilikan Manajerial Dan Konservatisme Akuntansi - Adelia Mega Jayanti; Soemaryono (INTELLECTUAL CAPITAL, Jurnal Akuntansi Kontemporer, 2024)
The purpose of the written research is to find out the effect of capital intensity, risk of lawsuits, and management ownership on accounting conservatism in chemical and basic manufacturing companies listed on the Indonesia Stock Exchange in 2019–2021. The written research sample consists of 96 annual reports and is based on quantitative data with sampling criteria using a research approach involving 32 basic and chemical manufacturing companies listed on the Indonesia Stock Exchange in 2019–2021. Written research covers basic chemical and industrial manufacturing businesses listed on the Indonesia Stock Exchange from 2019 to 2021. Descriptive statistical analysis, classical assumption tests (normality test, multicorrelation test, autocorrelation test, and heteroscedasticity test), multiple linear regression analysis, F test, analysis of the coefficient of determination (R2), and hypothesis testing (t), namely analysis techniques in written research. These techniques are used in conjunction with IBM SPSS Statistics Version 21 software. Conservatism in accounting is a preventative approach to future corporate financial reporting. It takes a lot of fixed assets for a business to generate sales, and that requires capital. Inaccuracies in financial reporting that harm creditors and investors are considered a source of risk of lawsuits. The number of shares owned by the manager represents managerial ownership. Therefore, the results regarding capital intensity, risk of lawsuits, and managerial ownership of accounting conservatism have little effect.